Estimation of Bearing Capacity of Pile with Variation of Shape on Cohesive Soil Based on the Result of CPT Test (Study Case: Gunung Anyar District) - Dian Purnamawati Solin; Fithri Estikhamah (Nusantara Science and Technology Proceedings, 2021)
The bearing capacity of soil provides the most important output for soil investigation. Bearing capacity becomes a reference in designing the substructure of the structure. Therefore, it is necessary to have a capable bearing capacity analyzed by varying the shape of the foundation to provide a clear description of the highest bearing capacity of all the variations presented. In this study, a soil investigation was carried out by using the Cone Penetration Test from several distribution locations in Gunung Anyar District Area, where it is well known as cohesive soil which has a lower bearing capacity compared to non-cohesive soil. Based on this analysis, it shows that the pile foundation using a square cross-section will provide a greater value for the pile bearing capacity. Increasing the dimensions of the cross-sectional shape, it will provide a greater value for the carrying capacity of the pile as well. This is evidenced at a depth of 16.4 m, for a square cross-sectional dimension of 0.4 m it gives a value of 80.49 tons, while for a cross-sectional dimension of 0.6 m it gives a value of 164.736 tons.